PARAMETRIC IDENTIFICATION OF HEAT-EXCHANGE AT HORIZONTAL CONTINUOUSLY STEPPING CASTING OF ZINC BAR - E. I. Marukovich; V. A. Pumpur; Ju. V. Petrunja (Литьë и металлургия)
In the article there are presented the results of the experimental-theoretical identification of the parameters of contact heat exchange of the process of the continuous horizontal pace casting of zink bar in metal crystallizer with water cooling.